Livros em castelhano na livraria de D. Teodósio I (1510?-1563) 5º Duque de Bragança (Estudios Humanísticos. Historia, 2013)
RESUMO Este ensaio insere-se no estudo dos conteúdos da livraria do duque D. Teodósio, no âmbito do Projecto De Todas as Partes do Mundo, O património do 5.º Duque de Bragança, D. Teodósio I , projecto de estudo integral do património do duque, com base em cópia seiscentista do inventário realizado à sua morte (1563). Este texto tem como objectivos avaliar a dimensão da livraria ducal por comparação com outras livrarias régias e aristocráticas da época, e sublinhar um dos seus traços mais significativos: a muito importante componente de livros em língua castelhana, testemunhando a interacção e circulação cultural no mundo hispânico no século XVI.Abstract: Castilian books in the library of duke D. Teodósio I (1510?-1563) of Bragança An Hispanic and European dimension This article is part of the ongoing investigation of the duke D. Teodósio’s library, in the context of the Project De Todas as Partes do Mundo, O património do 5.º Duque de Bragança, D. Teodósio I . This project aims to study the houlsehold and assets of the duke based on the post-mortem inventory. The goals of this article are to evaluate the real dimension of this library, in a comparative perspective with other aristocratic libraries of the time; and to underline the importance of Castilian books in this library, which is an eloquent testimony of the cultural interaction between Portugal and Spain in the sixteenth century.